16. Jahrestagung der Internationalen Kommission für die Fischerei im Nordwestatlantik (ICNAF) - Meßtorff, J. (1966)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010